2017
DOI: 10.1159/000452788
|View full text |Cite
|
Sign up to set email alerts
|

Use of Transcutaneous Bilirubin to Determine the Need for Phototherapy in Resource-Limited Settings

Abstract: Background: Routine and timely determination of total serum bilirubin (TSB) remains a challenge in many resource-limited countries with substantial burden of severe neonatal hyperbilirubinemia. Limited evidence exists on the potential usefulness of transcutaneous bilirubin (TcB) to identify infants who may require phototherapy based on possible treatment criteria in such settings. Objective: To compare the number of infants requiring phototherapy across different TSB criteria and determine the predictive perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“… 22 A study from Nigeria estimated the proportion of neonates born at term that met the criteria for phototherapy, according to different guidelines that were based on total serum bilirubin measured between 24 and 120 h after birth. 23 Those findings showed that 2.7%, 1.1%, 0.4%, and 5.4% of neonates, respectively, required phototherapy based on the criteria from the American Academy of Pediatrics (AAP), the National Institute for Health and Clinical Excellence, UK, the World Health Organization, or an absolute threshold of ≥12 mg/dl (205 µmol/l). 23 Another study showed that “clinicians provided phototherapy to only 54% of term infants with hyperbilirubinemia for whom it was recommended by the AAP”.…”
Section: Discussionmentioning
confidence: 99%
“… 22 A study from Nigeria estimated the proportion of neonates born at term that met the criteria for phototherapy, according to different guidelines that were based on total serum bilirubin measured between 24 and 120 h after birth. 23 Those findings showed that 2.7%, 1.1%, 0.4%, and 5.4% of neonates, respectively, required phototherapy based on the criteria from the American Academy of Pediatrics (AAP), the National Institute for Health and Clinical Excellence, UK, the World Health Organization, or an absolute threshold of ≥12 mg/dl (205 µmol/l). 23 Another study showed that “clinicians provided phototherapy to only 54% of term infants with hyperbilirubinemia for whom it was recommended by the AAP”.…”
Section: Discussionmentioning
confidence: 99%
“…40 Similar results have been observed by Olusanya and Emokpae. 41 The TcB values inform the health care professional about two questions: "Should I worry about this infant?" and "Should I obtain a TSB in this infant?".…”
Section: Transcutaneous Bilirubinometrymentioning
confidence: 99%
“…However, publications reporting outcomes of neonates treated following these dynamic treatment thresholds are still rare. 16 The Shoklo Malaria Research Unit (SMRU) set up a special care baby unit (SCBU) in 2008 in Mae La, the most populous refugee camp along the Thailand-Myanmar border, to provide basic care for neonates including oxygen, intravenous antibiotics, nasogastric feeding, phototherapy and basic laboratory tests. 17 Starting 2011, another two SCBUs were set up in clinics for migrant populations.…”
Section: What This Study Adds?mentioning
confidence: 99%